Electrocatalytic Hydrogen Production Trilogy. (18th March 2021) - Li, Yan; Wei, Xinfa; Chen, Lisong; Shi, Jianlin
Abstract: H2 production via water electrolysis is of great significance in clean energy production, which, however, suffers from the sluggish kinetics of the anodic oxygen evolution reaction (OER). Moreover, the anode product, O2, which is of rather low value, may lead to dangerous explosions and the generation of membrane‐degrading reactive oxygen species. Herein, to address these issues of electrocatalytic H2 production, we summarize the most recent advances in three stages based on the benefit increments and various electron donation routes, which are: 1) electron donation by traditional OER: developing efficient catalysts for water oxidation to promote H2 production; 2) electron donation by the oxidation of sacrificial agents: using sacrificial agents to assist H2 production; 3) electron donation by electrosynthesis reaction: achieving electrosynthesis in parallel with cathodic H2 production. Present challenges and related prospects will also be discussed, hopefully to benefit the further progress of electrocatalytic H2 generation. Abstract : Three stages of high‐efficient, low‐cost, and energy‐saving electrochemical hydrogen production are described in this Review based on the benefits and electron donation routes (donators) for hydrogen evolution. Future developments in electrocatalytic hydrogen production should benefit from these insights.